18.42% efficiency polymer solar cells enabled by terpolymer donors with optimal miscibility and energy levels. Issue 14 (8th March 2022) - Liao, Zhihui; Hu, Dingqin; Tang, Hua; Huang, Peihao; Singh, Ranbir; Chung, Sein; Cho, Kilwon; Kumar, Manish; Hou, Licheng; Chen, Qianqian; Yu, Weiyang; Chen, Haiyan; et al.
Abstract : A thiazole-functionalized terpolymer donor enables 18.4% efficiency polymer solar cells. Abstract : The rapid development of non-fullerene acceptors (NFAs) has placed increasing demands on polymer donors and there is still room for optimization of the currently available top-performing polymer donors to work perfectly with the state-of-the-art NFAs. To further develop and fine-tune the best-performing polymer donors, random ternary copolymerization is a simple and powerful strategy, in which the search for a suitable and easily accessible third component is the challenge. Herein, a series of terpolymer donors OPz11, OPz12, OPz13 and OPz14 are synthesized by incorporating varying fractions of the ester-substituted thiazole (E-Tz) unit into the D18 polymer. Notably, the subtle E-Tz content brings optimization in the energy levels, electrostatic potentials (ESPs), molecular aggregation, miscibility and morphology, as revealed by the open circuit voltage ( V OC ) improvement from 856.1 to 865.3 mV, and fill-factor (FF) enhancement from 74.34% to 78.71%. Finally, an exciting power conversion efficiency (PCE) of 18.42% is obtained from OPz11:Y6 devices, and is among the highest values reported for PSCs. This work illustrates that the accessible E-Tz unit is a promising building block to construct terpolymer donors for high-performance organic photovoltaic cells, and random ternary copolymerization is a flexible and promising strategy for photovoltaic materials development.